2016
DOI: 10.3892/ol.2016.4893
|View full text |Cite
|
Sign up to set email alerts
|

Spheres from cervical cancer cells display stemness and cancer drug resistance

Abstract: Abstract. Cervical cancer is one of the most common gynecological malignant tumors and is the cause of a serious health problem worldwide. An increasing amount of evidence has shown that cancer stem cells (CSCs) are present in tumors, and that these CSCs may be responsible for tumor metastasis and relapse. The present study aimed to identify and characterize a CSC population from the CaSki cell line. First, a stem cell culture medium was used to selectively expand the cancer stem-like cell spheres, and the put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…Thus, further studies are important to clarify the potential of the ABCG2 transporter in anti‐cancer drug efflux dependent on cellular conditions such as adherent and 3D culture. Previous reports have shown that 3D culture conditions induce cancer cells to develop CSC phenotypes such as high expression of CSC markers and anti‐cancer drug resistance in some cancer cells . In the same fashion, PDAC cells converted into ABCG2+ cells possessing stemness and anti‐cancer drug resistance by 3D culture conditions in this study.…”
Section: Discussionsupporting
confidence: 72%
“…Thus, further studies are important to clarify the potential of the ABCG2 transporter in anti‐cancer drug efflux dependent on cellular conditions such as adherent and 3D culture. Previous reports have shown that 3D culture conditions induce cancer cells to develop CSC phenotypes such as high expression of CSC markers and anti‐cancer drug resistance in some cancer cells . In the same fashion, PDAC cells converted into ABCG2+ cells possessing stemness and anti‐cancer drug resistance by 3D culture conditions in this study.…”
Section: Discussionsupporting
confidence: 72%
“…Cervical cancer is one of the most common malignancies diagnosed in women [ 173 , 174 , 175 ]. Chronic infection with high-risk human papillomavirus and inherited polymorphism of cytokine genes are involved in cervical cancer emergence [ 176 , 177 , 178 , 179 , 180 ].…”
Section: Chrysin and Cancermentioning
confidence: 99%
“…Moreover, in many underdeveloped countries routine screening may not be widely available due to limited resources ( Denny et al, 2006 ). Although new chemotherapeutic agents have been developed to slow down the progression of the disease, the number of cancer related deaths is still high because of drug-resistance and metastasis ( Liu et al, 2016 ; Siegel et al, 2016 ). Also, conventional treatments for cervical cancer are expensive ( Subramanian et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%